2017
DOI: 10.1111/nph.14758
|View full text |Cite
|
Sign up to set email alerts
|

The miR156SPL4 module predominantly regulates aerial axillary bud formation and controls shoot architecture

Abstract: Grasses possess basal and aerial axillary buds. Previous studies have largely focused on basal bud (tiller) formation but scarcely touched on aerial buds, which may lead to aerial branch development. Genotypes with and without aerial buds were identified in switchgrass (Panicum virgatum), a dedicated bioenergy crop. Bud development was characterized using scanning electron microscopy. Microarray, RNA-seq and quantitative reverse transcription polymerase chain reaction (RT-qPCR) were used to identify regulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 58 publications
1
55
0
Order By: Relevance
“…As negative regulators, miRNAs could repress target gene expression through post-transcriptional degradation and translational repression and play indispensable roles in diverse stress responses [42,43]. MicroRNA156, as previously reported, was involved in a variety signalling pathways by inhibiting SPL gene family members [16,19,23,36,44]. In Arabidopsis, 11 of 17 SPL genes were predicted to be miR156/miR157 targets [23].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…As negative regulators, miRNAs could repress target gene expression through post-transcriptional degradation and translational repression and play indispensable roles in diverse stress responses [42,43]. MicroRNA156, as previously reported, was involved in a variety signalling pathways by inhibiting SPL gene family members [16,19,23,36,44]. In Arabidopsis, 11 of 17 SPL genes were predicted to be miR156/miR157 targets [23].…”
Section: Introductionmentioning
confidence: 75%
“…However, these SPL genes showed signi cant difference in gene size and structure, so that there are signi cant differences in their functions. Previous studies have shown that SPL genes exhibit functional diversity in different plant species, including shoot architecture [15], axillary bud formation [16], plant architecture [17][18][19][20], male fertility [21], owering regulation [7,[22][23][24][25], in orescence branching [24,26], organ size [27][28][29][30] and grain yield [17,27]. In Arabidopsis, AtSPL3 has been rst identi ed gene and involved in the oral transition [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast to the extensive studies in Arabidopsis , little information is available regarding the roles of SPLs related to flowering in grasses. To date, only a few SPL s have been investigated in the regulation of the other development processes in grasses, including grain size and shape in rice (Wang et al ., 2015b; Si et al ., ), panicle branching in rice (Jiao et al ., ; Miura et al ., ) and axillary bud formation in switchgrass (Gou et al ., ). In the present study, we demonstrated that SPL7 and SPL8 redundantly regulated flowering in switchgrass.…”
Section: Discussionmentioning
confidence: 97%
“…Shoot apical meristem (SAM) or inflorescence samples were harvested and immediately fixed in 3% glutaraldehyde (in 25 mM phosphate buffer, pH 7.0) overnight and dehydrated in a graded ethanol series. The fixed, dried and sputter‐coated samples were observed by using scanning electron microscopy (SEM) as reported previously (Gou et al ., ).…”
Section: Methodsmentioning
confidence: 97%